A Novel Insight into the Role of PLA2R and THSD7A in Membranous Nephropathy. (15th July 2021) - Zhang, Pingna; Huang, Weijun; Zheng, Qiyan; Tang, Jingyi; Dong, Zhaocheng; Jiang, Yuhua; Liu, Yuning; Liu, Weijing
Abstract : Membranous nephropathy (MN) is an organ-restricted autoimmune disease mainly caused by circulating autoantibodies against podocyte antigens, including the M-type phospholipase A2 receptor (PLA2R) and thrombospondin domain-containing 7A (THSD7A). Antibodies against PLA2R are present in 70%–80% and against THSD7A in 2% of adult patients, which provides a paradigm shift in molecular diagnosis and management monitoring. Both antigens share some similar characteristics: they are expressed by podocytes and have wide tissue distributions; they are bound by autoantibodies only under nonreducing conditions, and the subtype of most autoantibodies is IgG4. However, the factors triggering autoantibody production as well as the association among air pollution, malignancy, and the pathogenesis of MN remain unclear. In this review, we discuss the similarity between the pathological mechanisms triggered by disparate antigens and their associated diseases. Furthermore, we demonstrated the possibility that PM2.5, malignancy, and gene expression specifically induce exposure of these antigens through conformational changes, molecular mimicry, or increased expression eliciting autoimmune responses. Thus, this review provides novel insights into the pathological mechanism of MN.